Clinical predictors of donor antibody titre and correlation with recipient antibody response in a COVID‐19 convalescent plasma clinical trial. (3rd November 2020) - Madariaga, M. L. L.; Guthmiller, J. J.; Schrantz, S.; Jansen, M. O.; Christensen, C.; Kumar, M.; Prochaska, M.; Wool, G.; Durkin‐Celauro, A.; Oh, W. H.; Trockman, L.; Vigneswaran, J.; et al.
Abstract: Background: Convalescent plasma therapy for COVID‐19 relies on transfer of anti‐viral antibody from donors to recipients via plasma transfusion. The relationship between clinical characteristics and antibody response to COVID‐19 is not well defined. We investigated predictors of convalescent antibody production and quantified recipient antibody response in a convalescent plasma therapy clinical trial. Methods: Multivariable analysis of clinical and serological parameters in 103 confirmed COVID‐19 convalescent plasma donors 28 days or more following symptom resolution was performed. Mixed‐effects regression models with piecewise linear trends were used to characterize serial antibody responses in 10 convalescent plasma recipients with severe COVID‐19. Results: Donor antibody titres ranged from 0 to 1 : 3892 (anti‐receptor binding domain (RBD)) and 0 to 1 : 3289 (anti‐spike). Higher anti‐RBD and anti‐spike titres were associated with increased age, hospitalization for COVID‐19, fever and absence of myalgia (all P < 0.05). Fatigue was significantly associated with anti‐RBD ( P = 0.03). In pairwise comparison amongst ABO blood types, AB donors had higher anti‐RBD and anti‐spike than O donors ( P < 0.05). No toxicity was associated with plasma transfusion. Non‐ECMO recipient anti‐RBD antibody titre increased on average 31% per day during the first three days post‐transfusion ( P = 0.01) and anti‐spike antibody titre by 40.3% ( P = 0.02). Conclusion: Advanced age, fever, absence of myalgia, fatigue, blood type and hospitalization were associated with higher convalescent antibody titre to COVID‐19. Despite variability in donor titre, 80% of convalescent plasma recipients showed significant increase in antibody levels post‐transfusion. A more complete understanding of the dose‐response effect of plasma transfusion amongst COVID‐19‐infected patients is needed. Abstract :